Situation Report: Czechoslovakia, 10 September 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Harvest below Expectations: Import Problems The Pharmaceutical Industry: Integration within Comecon Thirty Years of the State Film Industry Dissatisfaction with Performance of Mass Media